Penerapan senam sebagai upaya menurunkan tekanan darah pada penderita hipertensi di Desa Sukajaya Lempasing Kabupaten Pesawaran - Winarno, Rudi; Ladin, Juliawan; Sintia, Monica Bela Dwi; Natalia, Mutiara; Adhani, Neisa; Istawala, Anggun; Prayogo, Idfy Dwi; Fajrianti, Endah; Alam, Rama Rajasa Ferlanda; Saraswati, Ika (JOURNAL of Public Health Concerns, 2025)
Background: Hypertension is a non-communicable disease that ranks among the leading causes of death worldwide. According to 2023 WHO data, the global prevalence of hypertension reached 33%, while in Indonesia it stood at 30.8%. In Pesawaran Regency, the Hanura Community Health Center reported 1,749 cases of hypertension, making it the fifth most common disease. In Dusun 7 Mutun, 58% of the 69 households are affected by hypertension. One non-pharmacological approach proven effective in lowering blood pressure is hypertension exercise. Purpose: Reducing Blood Pressure in Hypertensive Patients Through a Hypertension Exercise Intervention. Method: The intervention was conducted over three days (May 14–16, 2025) in Dusun 7 Mutun, Sukajaya Lempasing Village, Pesawaran Regency. Ten hypertensive respondents participated. The program included a brief educational session and practical hypertension exercises. Evaluation involved measuring participants’ blood pressure before and after the intervention (pre-test and post-test). Results: Obtaining a mean pre-test systolic blood pressure value of 155.5 mmHg with a standard deviation of 11,891 and a mean post-test value of 132.5 mmHg with a standard deviation of 11,365. While the mean pre-test diastolic blood pressure value was 96.0 mmHg with a standard deviation of 6,992 and a mean post-test value of 79.0 mmHg with a standard deviation of 7,379. Conclusion: Hypertension exercise has been proven effective as a non-pharmacological intervention for reducing blood pressure.   Suggestion: Hypertension exercise should be implemented on an ongoing basis as an integral part of the community’s healthy lifestyle. Keywords: Blood pressure; Hypertension; Hypertension exercise; Non-pharmacological intervention Pendahuluan: Hipertensi merupakan salah satu penyakit tidak menular yang menjadi penyebab utama kematian di dunia. Data WHO tahun 2023 mencatat prevalensi hipertensi secara global mencapai 33%, sedangkan di Indonesia mencapai 30.8%. Di Kabupaten Pesawaran, data dari Puskesmas Hanura mencatat 1,749 kasus hipertensi, menempati urutan kelima penyakit terbanyak. Dan di Dusun 7 Mutun, 58% dari 69 keluarga mengalami hipertensi. Salah satu pendekatan nonfarmakologis yang terbukti efektif dalam menurunkan tekanan darah adalah senam hipertensi. Tujuan: Menurunkan tekanan darah pada penderita hipertensi melalui intervensi senam hipertensi. Metode: Kegiatan dilakukan selama tiga hari (14-16 Mei 2025) di Dusun 7 Mutun, Desa Sukajaya Lempasing, Kabupaten Pesawaran. Melibatkan 10 responden penderita hipertensi. Intervensi dilakukan dalam bentuk edukasi singkat dan praktik senam hipertensi. Evaluasi dilakukan dengan mengukur tekanan darah sebelum dan sesudah intervensi (pre-test dan post-test). Hasil: Mendapatkan nilai mean tekanan darah sistolik pre-test sebesar 155.5 mmHg dengan standar deviasi 11.891 dan nilai mean post-test sebesar 132.5 mmHg dengan standar deviasi 11.365. Sedangkan nilai mean tekanan darah diastolik pre-test sebesar 96.0 mmHg dengan standar deviasi 6.992 dan nilai mean post-test sebesar 79.0 mmHg dengan standar deviasi 7.379. Simpulan: Senam hipertensi terbukti efektif sebagai intervensi nonfarmakologis yang dapat menurunkan tekanan darah. Saran: Senam hipertensi perlu diterapkan secara berkelanjutan sebagai bagian dari gaya hidup sehat masyarakat.